Workplace Age Discrimination and Affecting Factors in Turkey: A Validation Study. Issue 5 (20th October 2021) - Özmete, Emine; Pak, Melike; Duru, Serdarhan
ABSTRACT: Objective : This study was undertaken to adapt Workplace Age Discrimination Scale (WADS) to Turkish. Methods : The sample of the study was composed of 465 volunteered women and men (18+ years) who had an active working life. Corrected item total correlation and Cronbach's alpha internal consistency coefficient were calculated for reliability of WADS. High order confirmatory factor analysis was performed to test the theoretical suitability and construct validity for Turkish context. Results : In this study, WADS has one factor construction. Cronbach's Alpha Reliability Coefficient was found as 0.904 for WADS. Predictors of workplace age discrimination in Turkish population were determined as age, hierarchical structure, job satisfaction, and income satisfaction Conclusion : These results showed that the Turkish version of WADS may be used as a valid and reliable tool in determining workplace age discrimination and in other relevant research. Exploring the validity and reliability of the scale should be repeated in groups who have different socio-demographics and health situations.